2019
DOI: 10.1016/j.jcot.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Radiological evaluation of tunnel position in single bundle anterior cruciate ligament reconstruction in the Indian population and their clinical correlation

Abstract: Background: Proper positioning of osseous tunnels during single bundle arthroscopic ACL reconstruction, which gives reproducibly good clinical outcome, is a matter of concern. Little evidence is there correlating tunnel position in arthroscopic ACL reconstruction with their clinical outcome in Indian population. Our aim in this study was to examine if the radiological tunnel-positions were significantly associated to the clinical outcomes. Methods: ACL reconstruction was performed in 147 young patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…In this study, the mean tunnel location in AP plane (lateral X-ray view) was at 80.01% [Table 3], which was similar to the study of Pinczewski et al and Debnath et al [11,19] In contrast to our study, Nema et al placed femoral tunnels at an average of 69.41% ± 10.77% posterior along the Blumensaat's line, which was more anterior to ours. [20] While in Pinczewski et al study, the midpoint of the femoral tunnel was located at a mean of 86% ± 5% posteriorly along Blumensaat's line, which was more posterior than our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the mean tunnel location in AP plane (lateral X-ray view) was at 80.01% [Table 3], which was similar to the study of Pinczewski et al and Debnath et al [11,19] In contrast to our study, Nema et al placed femoral tunnels at an average of 69.41% ± 10.77% posterior along the Blumensaat's line, which was more anterior to ours. [20] While in Pinczewski et al study, the midpoint of the femoral tunnel was located at a mean of 86% ± 5% posteriorly along Blumensaat's line, which was more posterior than our study.…”
Section: Discussionsupporting
confidence: 89%
“…[9] Studies have recommended placing the femoral tunnel at least 60-86% posterior along the Blumensaat's line. [11,[19][20][21] Considering this fact, we can conclude that 84% of tunnel made by combination of eyeballing and femoral offset aimer are correctly placed.…”
Section: Discussionmentioning
confidence: 99%
“…Debnath et al 21 did a radiological evaluation of the tunnel position in single-bundle ACLR in the Indian population and correlated with clinical outcome. They found that the “ideal clinical outcome” was significantly associated with placement of the femoral tunnel along the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Debnath et al 21 fizeram uma avaliação radiológica da posição do túnel na RCLA de feixe único na população indiana e a correlacionaram ao desfecho clínico. Estes autores descobriram que o “desfecho clínico ideal” estava significativamente associado à colocação do túnel femoral ao longo do plano sagital.…”
Section: Discussionunclassified